Comparative Study on Behavior of Self Compacting Concrete (SCC) under Static Load at Different Loading Rates - Nabilah , A.B.; Mohamed , M.A.W.; Nuraihan, Kamaruddin; Kalaikumar, V. (2010)
Self compacting concrete (SCC) was developed in late 1980s in order to improve the performance of concrete in its fresh state particularly when used in narrow formwork with congested steel reinforcement. The fundamental aims of the development were to enhance the flowability, self-compacting ability and segregation resistance using superplasticisers. This paper presents the results of the compressive and flexural behaviour of SCC beams tested under different loading rates. Cubes of SCC and normally compacted concrete (NC) were casted to test for compressive strength. A four-point static beam-load test was performed on SCC and NC beams subjected to the loading rates of 0.01 kN/s, 0.2 kN/s and 15 kN/s. Cube compressive strength, beam failure load, flexural modulus and the cracking pattern of SCC were obtained and compared with the normally compacted concrete. This study revealed that the hardened behavior of SCC is very similar to NC. In general, SCC developed higher early strength (compressive) as compared to NC of the same strength category. The maximum failure load of the SCC beam was also 6 to 9% higher than that of the NC beam for all loading rates. SCC exhibits longer non-linear behavior, which shows that it is very ductile compared to NC. SCC also developed less number of shear crack than NC, and the beams failed in flexure especially at high loading rate due to confinement effect.